QORAQALPOQ XALQI VA JAHON XALQLARINING OG‘ZAKI IJODIDAGI MUShTARAK JIHATLAR - Allambergenova, G. (SCIENCE and SOCIETY, 2023)
In the article, some aspects of the interrelation between the artistic oral creativity of the Karakalpak people and world folklore are analyzed based on the works of the Turkish scientist Pinar Fedakar. Also, the issue of studying Karakalpak folklore from a new point of view was discussed.
Keywords: folklore; Turkic studies; translations; Pinar Fedakar; analysis; genesis; general aspects